2016
DOI: 10.1039/c6cc04466b
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of a complex between β-glucopyranose and a macrocyclic receptor with dendritic multicharged water solubilizing chains

Abstract: Using commercial screens for crystallization of biomolecules and taking advantage of the use of racemic crystallography allowed the production of X-ray quality single crystals and the elucidation at 1.08 Å resolution of the solid state structure of a difficult target: the complex between glucopyranose and a water soluble macrocyclic receptor equipped with dendritic multianionic solubilizing chains.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 55 publications
2
26
0
Order By: Relevance
“…Our method employs a crystallization robot with a setup that is commonly used in protein crystallography, but only exceptionally in small molecule crystallography. 35 Initially, we chose a crystallization setup that consisted of 500 nl of the aqueous nearly saturated solution of the analyte; however repetitions of the crystallizations with just 150 and 100 nl of the analyte solutions were similarly successful. The last measurement series with 100 nl analyte solution required really minute amounts of material and still yielded high quality crystals (ESI Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Our method employs a crystallization robot with a setup that is commonly used in protein crystallography, but only exceptionally in small molecule crystallography. 35 Initially, we chose a crystallization setup that consisted of 500 nl of the aqueous nearly saturated solution of the analyte; however repetitions of the crystallizations with just 150 and 100 nl of the analyte solutions were similarly successful. The last measurement series with 100 nl analyte solution required really minute amounts of material and still yielded high quality crystals (ESI Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In parallel, the crystal structure of racemic ( 2 ) 2 ⊃ d/l ‐ 3 was elucidated (Figure c). The use of racemic crystallography recently helped delivering the very first structures of receptor–sugar complexes, but crystal growth is also a consequence of the complex structure being well defined in solution. There is a near‐perfect superposition of the ensemble of solution structures with the solid‐state crystallographic analysis with a root mean square deviation (rmsd) of 0.054±0.03 Å (Figure S17).…”
Section: Resultsmentioning
confidence: 99%
“…An advance brought by aromatic‐foldamer‐based saccharide receptors was straightforward access to detailed structural elucidation, including the very first characterization of complexes by single‐crystal X‐ray diffraction at atomic resolution. Crystal growth was facilitated by the rigid nature of the foldamer helices and by the use of racemic crystallography, through mixing the racemic sugar with the racemic host . Based on this structural information, we showed that it is possible to iteratively design a sugar receptor, that is, to introduce precise modifications so as to enhance selectivity in just a few rounds.…”
Section: Introductionmentioning
confidence: 99%
“…As shown by the X-ray crystal structure in Fig. 7, water-soluble versions of tetralactam B can nicely accommodate β-glucopyranose within the cavity [66]. There is a combination of hydrogen bonding between the equatorial sugar hydroxy groups and the receptor NH residues and also in the CH···π interactions with the hydrophobic anthrylene sidewalls.…”
Section: Reviewmentioning
confidence: 99%